Issues of the Development of Uzbek Cinema Art - Omonboevich, Kalandarov Izzat (International Journal of Membrane Science and Technology, 2023)
This scientific article analyzes the issues of the development of modern Uzbek cinema, studies their achievements and problems, makes the necessary suggestions and comments. In Uzbek art cinema, in the light of the current state of youth creativity, suggestions and comments will be made to eliminate existing problems.